2021
DOI: 10.1039/d1ra05955f
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial catalyzed green synthesis of tetrazoles and its derivatives: a review on recent advancements

Abstract: Tetrazoles are indispensable nitrogen containing heterocyclic scaffolds that offer a broad spectrum of applications in various domains such as medicinal chemistry, high energy material science, biochemistry, pharmacology etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 129 publications
(186 reference statements)
0
13
0
Order By: Relevance
“…The advancement of organic synthesis techniques has had a significant influence on the design and synthesis of innovative structures incorporating spirocyclic, polycyclic, and heterocyclic groups. The importance of these groups in the field of polymer chemistry has also arisen as an exceptionally promising domain due to the desirable qualities of them, such as enhanced mechanical strength, thermal stability, and electrical conductivity. One particular class of the heterocyclic compounds, known as tetrazoles, specifically nitrogenous heterocyclic 1,5-disubstituted-1 H -tetrazoles (1,5-DS-Ts), has been gaining significant attention due to its effectiveness in applications such as energy systems, nanomaterials, metal–organic frameworks, and medicinal compounds. , Despite the existence of diverse and complex libraries of 1,5-DS-Ts as small compounds, integrating them into polymer chemistry remains a challenging issue to be addressed. Indeed, it has been observed that the majority of currently available 1,5-DS-T containing polymers are predominantly composed of a carbon–carbon backbone with tetrazole side chains, rather than the main chain .…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of organic synthesis techniques has had a significant influence on the design and synthesis of innovative structures incorporating spirocyclic, polycyclic, and heterocyclic groups. The importance of these groups in the field of polymer chemistry has also arisen as an exceptionally promising domain due to the desirable qualities of them, such as enhanced mechanical strength, thermal stability, and electrical conductivity. One particular class of the heterocyclic compounds, known as tetrazoles, specifically nitrogenous heterocyclic 1,5-disubstituted-1 H -tetrazoles (1,5-DS-Ts), has been gaining significant attention due to its effectiveness in applications such as energy systems, nanomaterials, metal–organic frameworks, and medicinal compounds. , Despite the existence of diverse and complex libraries of 1,5-DS-Ts as small compounds, integrating them into polymer chemistry remains a challenging issue to be addressed. Indeed, it has been observed that the majority of currently available 1,5-DS-T containing polymers are predominantly composed of a carbon–carbon backbone with tetrazole side chains, rather than the main chain .…”
Section: Introductionmentioning
confidence: 99%
“…1b) as well as in agriculture and material engineering 107 as herbicides, plant growth regulators, explosives and energy storage devices. 20,23,[108][109][110] The rst tetrazole compound was prepared more than one hundred years ago, and then many scientists have introduced various synthetic strategies for preparation of these compounds. A 1,3-dipolar cycloaddition reaction is the most common method which takes place between azide ion or hydrazoic acid with various simple nitrile derivatives under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49] Likewise, tetrazole derivatives have various biological properties which are generally formed from [3 + 2] cycloaddition of azide and benzonitrile derivatives in the presence of practical catalysts. [50][51][52][53][54] Recently, 5-substituted tetrazoles are used as an isosteric replacement for carboxyl groups. [55] Tetrazole derivatives have various applications in coordination chemistry, organic chemistry, agriculture, the photographic industry, explosives, and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%